Pengaruh Dana Pihak Ketiga dan Total Aset Terhadap Laba Bank Syariah Indonesia - Kistiyaputri, Alifia (Jurnal Ekonomika dan Bisnis Islam, 2022)
Banks, like companies in general, have a goal to make a profit. Profit is also one of the assessments of the performance of a bank so that efforts are needed to maintain profit growth by taking into account the factors that influence it. Therefore, this study aims to determine the relationship between third party funds and total assets with the profit of Bank Syariah Mandiri. By using a quantitative approach and multiple linear regression data analysis techniques, this study has a population and sample that is Bank Syariah Mandiri. This study was analyzed using the IBM SPSS Statistics Version 20. The results showed that third party funds had a significant effect on earnings partially, which was indicated by a significant value of 0.015 < 0.05. While the total assets partially have no significant effect on profit as seen from the significance value of 0.059 > 0.05. Simultaneously third party funds and total assets have a significant effect on profit as seen from the significance value of 0.000 < 0.05. Based on the results of the coefficient of determination test, the amount of third party funds and total assets in describing profit is 42.3% while the remaining 57.7% is influenced by other variables that is not examined in this study.